摆线齿锥齿轮连续分齿法铣齿原理的研究 - 董学朱 (Jixie chuandong)
In this paper calculation formulas of differential change gear raito and index change gear raito for Oerlikon and Klingelnerg bevel gear generating machines are derived. Priciples of cutting epicycloid bevel gear by continuous indexing method are investigated systematically.